Effects of Intergenerational Social Support Exchange and Self-efficacy on Level of Depression among Elderly Women - Chung Mee Ko (Korean Society of Women Health Nursing, 2014)
PURPOSE: This study was to examine the effects of intergenerational social support exchange (providing social support, receiving social support) and self-efficacy on the level of depression among elderly women. METHODS: A cross-sectional survey design was used. The participants were 247 elderly women, over 60, living in Seoul. Data were collected by convenience sampling using self-reported questionnaires that consisted of items on general characteristics, depression, intergenerational social support exchange and self-efficacy. Data were analyzed with descriptive statistics, t-test, ANOVA, correlation, and multiple regression. RESULTS: Self-efficacy had the greatest impact on the level of depression among elderly women, followed by perceived health status and providing social support toward adult children. The model explained 39% of the variance. CONCLUSION: Results of the study suggest that as a way to prevent depression, the health administration needs to develop programs to enhance self-efficacy and to promote the supportive role of elderly women within the family.